2015
DOI: 10.1097/acm.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Patient Assessment of Medical Student Empathy

Abstract: The significant interaction effects of ethnicity and gender in clinical encounters, plus the inconsistencies observed between SPs' assessments of students' empathy and students' self-reported empathy, raise questions about possible ethnicity and gender biases in the SPs' assessments of medical students' clinical skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
4
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 20 publications
1
43
4
4
Order By: Relevance
“…For example, students’ ethnic background (white vs Asian American) was found to influence simulated patients’ assessments of empathic engagement in clinical encounters in OSCE stations (33). In a multi-institutional study by Berg and colleagues (35), inconsistencies were observed between simulated patients’ assessments (using JSPPPE scores) and students’ self-reported empathy (using JSE scores) (36). The inconsistencies were explained by significant interaction effects of gender and ethnicity (white, African American, Asian/Pacific Islander) of the simulated patients as well as the medical students (36).…”
Section: Correlation With Clinician’s Self-reported Empathymentioning
confidence: 99%
“…For example, students’ ethnic background (white vs Asian American) was found to influence simulated patients’ assessments of empathic engagement in clinical encounters in OSCE stations (33). In a multi-institutional study by Berg and colleagues (35), inconsistencies were observed between simulated patients’ assessments (using JSPPPE scores) and students’ self-reported empathy (using JSE scores) (36). The inconsistencies were explained by significant interaction effects of gender and ethnicity (white, African American, Asian/Pacific Islander) of the simulated patients as well as the medical students (36).…”
Section: Correlation With Clinician’s Self-reported Empathymentioning
confidence: 99%
“…Possibly, because women are hard-wired for maternity and parental care, they have been classically considered as more empathic than men (for an extensive review, see [ 3 ]). Psychological studies indeed report that women score higher than men on different self-reported measures of empathy in childhood [ 4 ], adolescence [ 5 , 6 ] and adulthood [ 7 9 ] with differences growing with age during the puberty period [ 5 , 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…of osteopathic medical education and equally matches the values of osteopathic patient-centered care.LimitationsAn important consideration when interpreting the results of the current study is that empathetic engagement realized through a developed patient-physician relationship may require more time than is available during a simulated encounter 26. Both the student and SP are aware of the nature of the encounter, thus potentially creating a false sense of rapport 27. This simulated situation may provide a confirmation bias whereby positive affirming behavior of both student and SP are influenced during the assessment.…”
mentioning
confidence: 98%